Needs Analysis to Design an English Blended Learning Program: Teachers’ and Administrators’ Voices - Luis Hernando Tamayo Cano; Andrés Felipe Riascos Gómez; Jorge Eduardo Pineda Hoyos (Profile: Issues in Teachers' Professional Development)
This needs analysis study sought to identify the contextual requirements to design and implement a blended learning program in English at a Colombian public university. Data on teachers’ and administrators’ perceptions were gathered through a questionnaire, interviews, and focus groups and analyzed using grounded theory. Findings revealed the need to invest considerably in new personnel and e-infrastructure. Likewise, students’ context should be considered to design EFL blended programs. Teachers and students should be offered ICT and methodological professional development. Finally, the program should carefully balance the integration of face-to-face and online modalities. This investigation can help the academic community of language educators and curriculum designers carry out needs analysis studies for creating contextualized blended learning programs.